Morphological characteristics and clinical significance of the distal femur in patients with hemophilia-related knee arthritis. Issue 47 (20th November 2020) - Gao, Qiang; Yao, Yunfeng; Jing, Juehua
Abstract : Abstract: This retrospective study aimed to define the morphological characteristics of the distal femur in patients with hemophilia-related knee arthritis (HA) and develop precise femoral component installation during total knee arthroplasty (TKA) using a reference axis. Computed tomography (CT) was performed in 75 patients [HA group: 34 patients, 48 knees; osteoarthritis (OA group): 41 patients, 48 knees] during 2017–2019. CT scans were constructed into three-dimensional models. We measured the medial (MPC) and lateral (LPC) posterior condyle widths, lateral anteroposterior (LAP) height, medial anteroposterior (MAP) height, mediolateral epicondyle (ML) width, and depths of the anterior patellar groove (X2) and the intercondylar notch (X4). Also, angles were measured between the posterior condylar line (PCL) and surgical transepicondylar axis (STEA) (PCA angle), anteroposterior axis (APA angle) and STEA (APSA angle), anterior condylar line (ACL) and STEA (ACA angle), and clinical transepicondylar axis (CTEA) and PCL (CTA angle). ML/MAP, ML/LAP, X4/LAP, X2/LAP, and LPC/ML ratios were calculated. There were no significant differences in any angles between the HA and OA groups ( P  > .05). However, the HA group had a smaller MPC ( P  < .05) and larger X4 than the OA group ( P  < .05). ML, ML/LAP, X2, MAP, and LAP showed no significant differences between the 2 groups. ML, ML/LAP, and PCA showed no significant differences between the 2 groups. During TKA in hemophilia-related knee arthritis patients, the femoral component can be installed with PCL as the reference axis, although individual differences should be considered.